THE IMPACT OF THE BASIC COMPONENTS OF ARCHITECTURE IN CREATING PLACE, WITH ECONOMIC POWER - Mohammad Mahdi Kalantarzade, Hossein Abbasimehr, pouyan berahman, Mahsa Mohammadpour (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Give that the issue of location is always one of the most important and at the same time challenging issue in the architecture field existed for centuries, architecture and architectural subjects including natural elements of the land are counted as particular. Therefore, they were clear explanations of the achievements of culture and included engineering and aesthetic developments of their time. The architecture of a place as a dynamic and ambiguous phenomenon is constantly changing and evolving. Political economy and other fundamental components affected by it, mentioned in this article can be indicators influencing change and transformation of architectural sites. Also, the need to include these components in terms of action is one of the challenges facing the architecture of the place. 1:Architecture and culture where architecture and arts are one of the most important tools for introducing cultures to other communities, thus it obtains the possibility to spread the values ??of a culture. 2:Digital Culture in Architecture Where architecture, as the most tangible art we face at any given time, has also been influenced by digital culture. 3:Architecture and the political economy of space where the discovery of architectural and spatial patterns of the production, distribution, consumption process and the role of governments, groups and social classes in shaping these patterns are found. 4:Architecture and branding of a place where the deliberate design of a specific and embodied image of any specified place tries to express a new meaning. 5:Architectural and tourism destinations (place marketing) where architecture can serve as a basic tool to simulate the development of the tourism industry in special areas. 6:Consumerism where architecture becomes a tool for behavioral economics. 7:Corporate architecture where architecture is used to differentiate the image of companies in the background of the agreement to improve their economic position in the market. 8:Architecture as a factor of evolution and integration in the local community.